2017
DOI: 10.1186/s12882-016-0422-4
|View full text |Cite
|
Sign up to set email alerts
|

Rationale, description and baseline findings of a community-based prospective cohort study of kidney function amongst the young rural population of Northwest Nicaragua

Abstract: BackgroundAn epidemic of Mesoamerican Nephropathy (MeN) is killing thousands of agricultural workers along the Pacific coast of Central America, but the natural history and aetiology of the disease remain poorly understood. We have recently commenced a community-based longitudinal study to investigate Chronic Kidney Disease (CKD) in Nicaragua. Although logistically challenging, study designs of this type have the potential to provide important insights that other study designs cannot. In this paper we discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 19 publications
1
30
1
Order By: Relevance
“…The rationale and description of the study design have been published elsewhere. 20 Briefly, this was a 2-year longitudinal, community-based study following 350 participants ages 18-30 years old in the Leon and Chinandega regions of Nicaragua (Figure 1). After engagement work, we performed a census of all adults ages 18-30 years old in nine rural communities.…”
Section: Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale and description of the study design have been published elsewhere. 20 Briefly, this was a 2-year longitudinal, community-based study following 350 participants ages 18-30 years old in the Leon and Chinandega regions of Nicaragua (Figure 1). After engagement work, we performed a census of all adults ages 18-30 years old in nine rural communities.…”
Section: Cohortmentioning
confidence: 99%
“…After exclusion of 4% of the potential participants because of self-reported CKD, diabetes, or hypertension, 350 participants (of the 360 invited after random selection of eligible women; 97%) were included in the study. 20 Overall, participants attended a total of 1581 study visits over the 2-year follow-up (92% of planned visits). Two participants died from ESRD during the study period.…”
Section: Cohort and Follow-upmentioning
confidence: 99%
“…The study rationale, design and baseline findings have been reported elsewhere (16,17). Briefly this was a population-representative, community-based follow-up study recruiting 350 men and women (ratio 3:1) aged 18-30 years without self-reported CKD or traditional CKD risk factors (diabetes or hypertension).…”
Section: Study Populationmentioning
confidence: 99%
“…Since 2014, our team has been conducting the first prospective community-based cohort study investigating the evolution and aetiology of MeN. The study initially recruited 350 healthy men and women (3:1 ratio), from 9 rural communities in north-western Nicaragua (16). Participants were invited to follow-up visits every 6 months (before and immediately after the sugarcane harvest).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation